Identificação de Unidades de Paisagem: metodologia aplicada a Portugal Continental - Teresa Pinto Correia; António Cancela Abreu; Rosário Oliveira (Finisterra - Revista Portuguesa de Geografia, 2001)
IDENTIFICATION AND CHARACTERISATION OF LANDSCAPE IN PORTUGAL –This paper presents the concepts and methodology used in the study «Identification and characterisation of landscape in continental Portugal» undertaken by theDepartment of Landscape and Biophysical Planning of the University of Evora for the General Directorate for Spatial Planning and Urban Development (DGOT-DU) at the Ministry of the Environment and Spatial Planning, between 1999 and 2001. On the one hand, the methodological approach developed is based on the methodologies used recently for the same purpose in different European countries and on the way landscape has been considered in various European documents in the last years. On the other hand, it is also based on the team’s concern to approach the landscape as an holistic entity, and to examine its various components: ecological, cultural, socio-economic and sensorial. The set aim has been to define landscape units and to characterize these units in relation to the present landscape and the recorded trends, related problems and possibilities. Thus, the cartography relative to selected variables has been combined and related to satellite images and field surveys. The results of cross-referencing all this information has than been combined with expert examination of landscape coherence and character within each unit. The assessment was completed after careful bibliographic research and consultation with regional experts. The result is a flexible approach that combines objective analysis with a more subjective assessment, which the team considered fundamental for a true understanding of landscape.